2017
DOI: 10.3390/dj5030025
|View full text |Cite
|
Sign up to set email alerts
|

Weight Status and Dental Problems in Early Childhood: Classification Tree Analysis of a National Cohort

Abstract: A poor quality diet may be a common risk factor for both obesity and dental problems such as caries. The aim of this paper is to use classification tree analysis (CTA) to identify predictors of dental problems in a nationally representative cohort of Irish pre-school children. CTA was used to classify variables and describe interactions between multiple variables including socio-demographics, dietary intake, health-related behaviour, body mass index (BMI) and a dental problem. Data were derived from the second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…While traditional predictive models such as logistic and linear regression are feasible, these models can have issues with their implementation and ultimately interpretation by healthcare providers with perceived "black box" results [8,9]. Classification and regression tree analysis (CART) is a technique that is gaining popularity within healthcare due to its ease of interpretation and implementation [8,[10][11][12][13][14][15] Common examples can be noted for guidelines on paediatric head trauma [16][17][18] and paediatric abdominal injuries [19][20][21]. Specifically, CART analysis starts with a large group of individuals, and then makes a series of binary node splits based on some criterion that improves group purity in order to effectively classify individuals.…”
Section: Classification and Regression Tree Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…While traditional predictive models such as logistic and linear regression are feasible, these models can have issues with their implementation and ultimately interpretation by healthcare providers with perceived "black box" results [8,9]. Classification and regression tree analysis (CART) is a technique that is gaining popularity within healthcare due to its ease of interpretation and implementation [8,[10][11][12][13][14][15] Common examples can be noted for guidelines on paediatric head trauma [16][17][18] and paediatric abdominal injuries [19][20][21]. Specifically, CART analysis starts with a large group of individuals, and then makes a series of binary node splits based on some criterion that improves group purity in order to effectively classify individuals.…”
Section: Classification and Regression Tree Analysismentioning
confidence: 99%
“…The use of a CART analysis and subsequent production of a classification tree for the care of individuals with lower limb prostheses is unique. There is growing popularity and use of classification trees across healthcare (e.g., see references [8,[10][11][12][13][14][15]). The classification tree developed in this analysis provides probability for determining a patient's functional potential.…”
Section: Model Strengthsmentioning
confidence: 99%
“…21,25 Aparentemente la presencia de un mayor consumo de alimentos si bien desencadena el incremento en el peso corporal reflejado en el IMC, también provocaría un estímulo en la secreción salival 26 provocando aumento en esta y por ende una acción de autoclisis de esta sobre el biofilm dental primer reservorio de los microrganismos, 27 lo que podría explicar los bajos índices de caries detectados en la población con peso elevado. 28 Como odontólogos se hace necesario guiar al paciente, a sus padres y/o responsables en los procesos de re-mineralización, este asesoramiento requiere involucrar la ejecución de hábitos de higiene y nutricionales 29 que como medida preventiva a la presencia de problemas en la cavidad oral, resulta básica.…”
Section: Discussionunclassified
“…In the last decade, several studies have analyzed the influence of nutrition on dental eruption [ 6 , 11 , 12 , 15 , 17 , 20 , 21 , 26 , 29 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Most studies found an association between being overweight and acceleration of tooth eruption, although it was not significant in all cases [ 6 , 12 , 37 , 39 , 42 ].…”
Section: Introductionmentioning
confidence: 99%